2023
DOI: 10.1073/pnas.2216820120
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin regulates central clock function and circadian responses to light

Abstract: Daily and annual changes in light are processed by central clock circuits that control the timing of behavior and physiology. The suprachiasmatic nucleus (SCN) in the anterior hypothalamus processes daily photic inputs and encodes changes in day length (i.e., photoperiod), but the SCN circuits that regulate circadian and photoperiodic responses to light remain unclear. Somatostatin (SST) expression in the hypothalamus is modulated by photoperiod, but the role of SST in SCN responses to light has not been exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…4 F – H ), with PS 50 values comparable to those for CRF-AVP –/– and Pomc-V1b –/– mice. During the preparation of our manuscript, other investigators also reported a similar phenotype of SST –/– mice ( 42 ). Behavioral analyses confirmed that the period length in DD, the phase angle from LD to DD, and the magnitude of phase shift after a short light pulse in SST m/m and SSTR1 –/– mice were essentially identical to those in WT mice ( SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 67%
“…4 F – H ), with PS 50 values comparable to those for CRF-AVP –/– and Pomc-V1b –/– mice. During the preparation of our manuscript, other investigators also reported a similar phenotype of SST –/– mice ( 42 ). Behavioral analyses confirmed that the period length in DD, the phase angle from LD to DD, and the magnitude of phase shift after a short light pulse in SST m/m and SSTR1 –/– mice were essentially identical to those in WT mice ( SI Appendix , Fig.…”
Section: Resultssupporting
confidence: 67%
“…Under normal physiological conditions, SST is mainly produced in the digestive and nervous systems ( 1 ). with its production in the brain following a circadian rhythm ( 21 ). Aberrant elevations of SST are evident in conditions such as somatostatinoma and inflammatory bowel diseases ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%